Nrf2 deficiency prevents reductive stress-induced hypertrophic cardiomyopathy - Kannan, Sankaranarayanan (Oxford University Press, 2013)
AIMS: Mutant protein aggregation (PA) cardiomyopathy (MPAC) is characterized by reductive stress (RS), PA (of chaperones and cytoskeletal components), and ventricular dysfunction in transgenic mice expressing human mutant CryAB (hmCryAB). Sustained activation of nuclear erythroid-2 like factor-2 (Nrf2) causes RS, which contributes to proteotoxic cardiac disease. The goals of this pre-clinical study were to (i) investigate whether disrupting Nrf2-antioxidant signalling prevents RS and rescues redox homeostasis in hearts expressing the mutant chaperone and (ii) elucidate mechanisms that could delay proteotoxic cardiac disease. METHODS AND RESULTS: Non-transgenic (NTG), transgenic (TG) with MPAC and MPAC-TG:Nrf2-deficient (Nrf2-def) mice were used in this study. The effects of Nrf2 diminution (Nrf2±) on RS mediated MPAC in TG mice were assessed at 6–7 and 10 months of age. The diminution of Nrf2 prevented RS and prolonged the survival of TG mice (∼50 weeks) by an additional 20–25 weeks. The TG:Nrf2-def mice did not exhibit cardiac hypertrophy at even 60 weeks, while the MPAC-TG mice developed pathological hypertrophy and heart failure starting at 24–28 weeks of age. Aggregation of cardiac proteins was significantly reduced in TG:Nrf2-def when compared with TG mice at 7 months. Preventing RS and maintaining redox homeostasis in the TG:Nrf2-def mice ameliorated PA, leading to decreased ubiquitination of proteins. CONCLUSION: Nrf2 deficiency rescues redox homeostasis, which reduces aggregation of mutant proteins, thereby delaying the proteotoxic pathological cardiac remodelling caused by RS and toxic protein aggregates.